Circular RNA_0057209 Acts as ceRNA to Inhibit Thyroid Cancer Progression by Promoting the STK4-Mediated Hippo Pathway via Sponging MicroRNA-183. (11th March 2022) - Peng, Xinzhi; Zhu, Yue; Lin, Shaojian; Yu, Weiming; Zhang, Cheng; Tan, Langping; Long, Miaoyun; Luo, Dingyuan; Ji, Chengcheng
Abstract : Thyroid cancer is the most common malignancy of the endocrine system, and its outcome remains unsatisfactory. In recent years, circular RNAs (circRNAs) have emerged as crucial regulators in cancers. In the current study, we aimed to investigate whether and how circRNA_0057209 functioned in thyroid cancer. Initial results revealed that circRNA_0057209 and STK4 were both reduced, while miR-183 was up-regulated in thyroid cancer tissues and cells. Experiments including RNA pull-down and RIP assays further identified that upregulation of circRNA_0057209 augmented the expression of STK4, a target gene of miR-183, by competitively-binding to miR-183. Furthermore, functional experiments provided evidence that overexpression of circRNA_0057209 not only inhibited the proliferative, migratory, and invasive properties of thyroid cancer cells while facilitating their apoptosis but also delayed tumor growth. Conversely, upregulation of miR-183 or silencing of STK4 reversed the changes induced by circRNA_0057209. Meanwhile, mechanistic experimentation demonstrated that circRNA_0057209 promoted STK4 expression by sponging miR-183, while STK4 enhanced YAP phosphorylation to mediate the Hippo pathway, thereby suppressing tumor progression. Altogether, our findings indicated that circRNA_0057209 may serve as a competing endogenous RNA of miR-183 to increase STK4 expression, thus inhibiting the development of thyroid cancer.